A new experimental method to measure and calculate the tensile strength of concrete - Chai, Qihui; Huang, Shasha; Wan, Fang; Wu, Feng; Feng, Lingyun (Frontiers in Materials, 2023)
A new method is introduced to test the tensile strength of concrete: the cylinder transverse splitting test. Compared with the cylinder splitting (or Brazilian) test, the cylinder transverse splitting test involves different load positions and offers the advantages of doubling the data volume with the same number of specimens and improving the detection accuracy. Finite element analysis software was used to simulate the concrete cylinder transverse splitting test and the stress distribution on the failure surface was determined. The results show that the fracture of a cylinder is mainly determined by tensile stress. The splitting strength of normal concrete and crumb rubber concrete, a new environmentally friendly concrete material that has gathered considerable attention in recent years, was obtained by cylinder transverse and cube splitting tests. The cylinder transverse splitting test data show a stable correlation with the cube splitting test data and well characterize the concrete strength. The relationship between the cylinder nominal transverse splitting strength () and cube splitting strength () was established on the basis of linear analysis of the test data: . The calculated cube splitting strength is in good agreement with the test values.